Consistency limits and compaction characteristics of clay soils containing rubber waste. Issue 2 (16th July 2018) - Soltani, Amin; Deng, An; Taheri, Abbas; Sridharan, Asuri
Abstract : The aim of the study reported in this paper was to develop practical correlative models capable of predicting the compaction characteristics of clay soils blended with rubber from waste vehicle tyres. Four different clay soils, ranging from intermediate to high plasticity, were adopted for the test programme and each was blended with four different percentages of ground rubber waste. The test programme consisted of cone penetration (consistency limits) and standard Proctor compaction tests. As a result of ground rubber inclusion, the consistency limits and compaction characteristics all exhibited a linear decreasing trend with increase in rubber content. The rate of decrease, however, was greater for the high-plasticity clays. Simple correlative models, linking the compaction characteristics to the consistency limits, were suggested and validated by statistical techniques. The proposed models provide a practical procedure towards predicting the compaction characteristics of ground rubber–clay blends without the hurdles of conducting laboratory compaction tests, and thus can be implemented in practice for preliminary assessments.